(untitled) - Agee, Jon (New York, 2013)
Little Santa loves the North Pole. The rest of his family? Not so much. So, when they decide to move to Florida, Santa is miserable. Lucky for him, a blizzard foils their plans. The only way out of the house is up the chimney. Up goes Santa, to look for help, and along the way, he meets a reindeer and a large group of elves, who are more than eager to join in the rescue! With the sly humor of Jon Klassen and the read-aloud pleasure of How the Grinch Stole Christmas, this tale of Santa’s beginnings is perfect for every kid’s holiday library.
Keywords: Children's literature, United states,Văn học thiếu nhi, Mỹ